Answer:
The angular velocity is 15.37 rad/s
Solution:
As per the question:
Horizontal distance, x = 30.1 m
Distance of the ball from the rotation axis is its radius, R = 1.15 m
Now,
To calculate the angular velocity:
Linear velocity, v =
v =
v =
v =
Now,
The angular velocity can be calculated as:
Thus
Answer:
The object's initial temperature is 333.6 K
Explanation:
We first assume that the liquid can only transfer heat to the object through convective heat transfer method.
Let T₀ = the initial temperature of the object
T = temperature of the object at anytime.
The rate of heat transfer from the liquid to the object is given as
Q = -hA (T∞ - T)
T∞ = temperature of the fluid = 400 K
A = Surface area of the object in contact with the liquid = 0.015 m²
h = Convective heat transfer coefficient is given to be = 10 W/(m²K)
The rate of heat gained by the object is given by
mC (d/dt)(T∞ - T)
m = mass of the object = ρV
ρ = density of the object = 100 kg/m³
V = volume of the object = 0.000125 m³
m = ρV = 100 × 0.000125 = 0.0125 kg
C = specific heat capacity of the object = 100 J/(kgK)
The rate of heat loss by the liquid = rate of heat gain by the object
-hA (T∞ - T) = mC (d/dt)(T∞ - T)
(d/dt)(T∞ - T) = - (dT/dt) ( Since T∞ is a constant)
- mC (dT/dt) = -hA (T∞ - T)
(dT/dt) = (hA/mC) (T∞ - T)
Let s = (hA/mC)
(dT/dt) = -s (T - T∞)
dT/(T - T∞) = -sdt
Integrating the left hand side from T₀ (the initial temperature of the object) to T and the right hand side from 0 to t
In [(T - T∞)/(T₀ - T∞)] = -st
(T - T∞)/(T₀ - T∞) = e⁻ˢᵗ
(T - T∞) = (T₀ - T∞)e⁻ˢᵗ
s = (hA/mC) = (10 × 0.015)/(0.0125×100) = 0.12
T = 380 K at t = 10 s
T₀ = ?
T∞ = 400 K
st = 0.12 × 10 = 1.2
(380 - 400) = (T₀ - 400) e⁻¹•²
(-20/0.3012) = (T₀ - 400)
(T₀ - 400) = - 66.4
T₀ = 400 - 66.4 = 333.6 K
Hope this Helps!!!
products. Which statement explains this difference in mass?
A. Some of the mass was transformed into neutrons during the
process.
O B. Mass was destroyed and disappeared during the process.
C. Some of the mass was transformed into gases during the
process.
D. Mass was transformed into energy during the process.
Answer:
D. Mass was transformed into energy during the process.
Answer:
C
Explanation:
Some of the mass
The force of gravity that the space shuttle experiences is 9.8 x 10^5 Newtons.
To calculate the force of gravity that the space shuttle experiences, we can use the equation F = mg, where F represents the force of gravity, m is the mass of the object, and g is the acceleration due to gravity (approximately 9.8 m/s² on Earth). In this case, the mass of the space shuttle is given as 1.0 x 10^5 kg. However, we need to convert the altitude of the shuttle into meters, so 200.0 km becomes 200,000 meters.
Now we can calculate the force of gravity:
F = (1.0 x 10^5 kg)(9.8 m/s²)
F = 9.8 x 10^5 N
Therefore, the space shuttle experiences a force of gravity of 9.8 x 10^5 Newtons.
#SPJ3
B No, the energy in the wave pushed the water particles from above the earthquake in the opposite direction.
C Yes, the water particles moved toward the island while the energy remained above the earthquake.
How many bright-dark-bright fringe shifts are observed as the cell fills with air?
Answer:
55.3
Explanation:
The computation of the number of bright-dark-bright fringe shifts observed is shown below:
where
d =
n = 1.00028
Now placing these values to the above formula
So, the number of bright-dark-bright fringe shifts observed is
= 55.3
We simply applied the above formula so that the number of bright dark bright fringe shifts could come
Answer:
96.05 N
Explanation:
From Vector,
The two forces acting along the x and y axis are perpendicular,
Fr = √(60²+75²) .............. Equation 1
Where Fr is the result of the two forces
Fr = √(3600+5625)
Fr = √(9225)
Fr = 96.05 N.
Note: Since the object moves with a constant velocity when it is acted upon by the three forces, The acceleration is zero and as such the resultant of the forces is equal to zero.
Therefore,
Ft = Fr+F3................... Equation 2
Where Ft = Total resistance of the three forces, F3 = magnitude of the third force.
make F3 the subject of the equation,
F3 = Ft-Fr
Given: Ft = 0 N, Fr = 96.05 N.
Substitute into equation 2
F3 = 0-96.05
F3 = -96.05 N.